Hubungan Faktor-Faktor Pemilihan Metode Kontrasepsi dengan Pemakaian Alat Kontrasepsi pada Program 1000 Hari Awal Kehidupan di Payangan Gianyar - Putu Niara Vinayah; I Gusti Ngurah Made Bayuningrat; Luh Gede Pradnyawati (Aesculapius Medical Journal, 2023)
The Maternal Mortality Rate (MMR) describes the well-being in a country. MMR in Indonesia keeps on increasing, becoming a concern to lower the Total Fertility Rate (TFR) with efforts to use contraception. Preliminary surveys found that there are still a lot of mothers in this program who have not used contraceptive methods. This study aims to determine the relationship of contraceptive method selection factors with the use of contraception in the program 1000 days early in life in Payangan Gianyar. The design used was analytical research with cross sectional approach. The study was conducted in Payangan Gianyar which is where the program is carried out with a sample number of 161 people. The research time will be carried out from December 2021 to March 2022. The data is obtained through the primary data of the questionnaire. The data will be analyzed in univariate, bivariate and multivariate. The results of the study in the bivariate test showed that there was a significant relationship between age, education level, parity, knowledge level, and birth control acceptor attitude with the use of contraceptives in the 1000 Days Early Life Program in Payangan Gianyar. However, there is no significant relationship between work, birth control information, and husband support. The results of the multivariate test analysis showed that the variables of age, education, knowledge and attitude of birth control acceptors had a significant relationship with the use of contraceptives. The hope is to be more optimized quality and quantity regarding health promotion regarding the use of contraceptives.